2018
DOI: 10.1016/j.neuroimage.2018.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Brain mechanisms underlying cue-based memorizing during free viewing of movie Memento

Abstract: How does the human brain recall and connect relevant memories with unfolding events? To study this, we presented 25 healthy subjects, during functional magnetic resonance imaging, the movie 'Memento' (director C. Nolan). In this movie, scenes are presented in chronologically reverse order with certain scenes briefly overlapping previously presented scenes. Such overlapping "key-frames" serve as effective memory cues for the viewers, prompting recall of relevant memories of the previously seen scene and connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 96 publications
1
31
0
Order By: Relevance
“…These findings demonstrate that perturbing one node of the episodic memory network can alter large-scale, multimodal patterns of neural activity which are considered to be fundamental to memory.Episodic memory is thought to critically depend on cortical reinstatement mediated by the hippocampus[1][2][3]. Consistent with prior research[9,27,34], we identified reinstatement of video-specific patterns of neural activity within a set of posterior parietal and occipital regions following control stimulation. A greater number of regions showed significant reinstatement…”
supporting
confidence: 88%
“…These findings demonstrate that perturbing one node of the episodic memory network can alter large-scale, multimodal patterns of neural activity which are considered to be fundamental to memory.Episodic memory is thought to critically depend on cortical reinstatement mediated by the hippocampus[1][2][3]. Consistent with prior research[9,27,34], we identified reinstatement of video-specific patterns of neural activity within a set of posterior parietal and occipital regions following control stimulation. A greater number of regions showed significant reinstatement…”
supporting
confidence: 88%
“…In one relevant study, Milivojevic et al (2016) used an audio-visual movie with interleaved storylines ("Sliding Doors") and found coding of storyline information in the hippocampus (but not in the DMN areas that are the focus of our study). In another relevant study, Kauttonen et al (2018) scanned participants who watched the movie "Memento", in which recurring cues were embedded to trigger memory recall, similar to the motifs in our story; they found that recurring scenes activated matching, scene-specific neural patterns in low-level sensory regions, and also that there was a common (i.e., not-scene-specific) neural pattern that was evoked in DMN regions whenever participants viewed a scene for a second time.…”
Section: Introductionmentioning
confidence: 94%
“…Our study resolves this confound because both storylines were presented auditorily by the same speaker and thus did not differ in low-level sensory properties. Likewise, a limitation of the design of Kauttonen et al (2018) is that recurring scenes were repeated exactly; as such, pattern similarity between matching cues could be due to matching sensory inputs (as opposed to memory). In contrast, in our study, recurring motifs were embedded in different scenes, making it easier to distinguish between the influences of perception and memory.…”
Section: Introductionmentioning
confidence: 99%
“…To study real-life sensory experience, neuroscientists are increasingly employing naturalistic paradigms such as dynamic videos, speech and music that incorporate sensory stimuli typically encountered in everyday life (Bartels and Zeki 2004, Hasson, Nir et al 2004, Wagner and Kelley 2016, Kauttonen, Hlushchuk et al 2018.…”
Section: Scientific Questions and Outline Of This Thesismentioning
confidence: 99%
“…Analysis using MVPA identified patterns of activation in higher-order cortical network (precuneus, angular gyrus, cingulate gyrus, frontal poles) during presentation of key-frame scenes which revealed contextual information about prior events. This clever use of (re-)editing a film design provides a unique insight into the pattern of brain activity in recalled memories which connect a narrative to its relevant context (Kauttonen, Hlushchuk et al 2018).…”
Section: Contextual Memorymentioning
confidence: 99%